THE EFFECT OF DARK CHOCOLATE CONSUMPTION TO LOWERING BLOOD PRESSURE IN THE ELDERLY WITH HIPERTENSION: CASE REPORT - Sahla Nurannisa; Annas Sumeru; Akhyarul Anam (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Introduction: Hypertension is a disease of the cardiovascular system with a prevalence that continues to increase rapidly, especially in several developing countries including Indonesia. The incidence of hypertension tends to be high in the elderly as a degenerative effect that occurs with age. The main cause of uncontrolled hypertension in the elderly is that elderly people with hypertension refuse to undergo treatment, so the blood pressure in their body becomes uncontrollable. This is because elderly people cannot tolerate the side effects experienced after taking blood pressure medication. Therefore, it is necessary to introduce another alternative therapy to treat hypertension in the elderly, namely by consuming dark chocolate. Purpose: Knowing the effect of eating dark chocolate to reduce blood pressure in elderly people with hypertension. Methods: Case study by applying implementation according to evidencebased practice in nursing care. In the intervention session, respondents will be asked to consume 72% dark chocolate as much as 30 grams for 7 consecutive days. The tool used to measure blood pressure is an automatic Sphygmomanometer. Keywords used: dark chocolate, hypertension, and elderly. Discussion: Dark chocolate contains flavonoids that are thought to increase endothelial nitric oxide, improve the elasticity of blood vessels and blood circulation. The benefits of flavonoids can also lower blood pressure in elderly people suffering from high blood pressure. Conclusion: There is an effect of giving dark chocolate on lowering blood pressure in elderly people with hypertension based on the results of blood pressure measurements before and after the intervention during the intervention period. the results of blood pressure measurements before and after giving the intervention for 7 days.